1996
DOI: 10.1016/s0035-9203(96)90442-3
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind clinical trial of two antivenoms in patients bitten by Bothrops atrox in Colombia

Abstract: A randomized double-blind clinical trial in 39 patients envenomed by Bothrops atrox in Antioquia and Chocó, Colombia, was performed to compare the efficacy and safety of 2 equine-derived antivenoms prepared at Instituto Clodomiro Picado, University of Costa Rica. Twenty patients received a monovalent anti-B. atrox antivenom (group A) and 19 patients were treated with a polyvalent (Crotalinae) antivenom (group B). Both antivenoms were equally efficient in the neutralization of the most relevant signs of envenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
13

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 18 publications
5
44
0
13
Order By: Relevance
“…Clinical investigations have demonstrated the efficacy of these products on the neutralization of life-threatening systemic effects associated with these envenomations (3,5,14). However, experimental and clinical evidence indicates that local effects in Bothrops sp envenomations are poorly neutralized by these and other antivenoms (3,8,10,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical investigations have demonstrated the efficacy of these products on the neutralization of life-threatening systemic effects associated with these envenomations (3,5,14). However, experimental and clinical evidence indicates that local effects in Bothrops sp envenomations are poorly neutralized by these and other antivenoms (3,8,10,13).…”
Section: Discussionmentioning
confidence: 99%
“…The use of these products has greatly contributed to the reduction of mortality owing to their effectiveness in the neutralization of life-threatening, systemically acting toxins present in snake venoms (2)(3)(4). Randomized controlled clinical trials have demonstrated that antivenoms are highly effective in halting systemic bleeding, coagulopathies and other cardiovascular disturbances due to envenomations by snakes of the family Viperidae in Latin America (3,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 36 % of all patients with Bothrops bites only present local envenoming, without systemic manifestations (Otero et al 1992a;Otero 1994Otero , 2007Otero , 2014OteroPatiño 2009). On the basis of previous studies performed in Colombia in B. asper bites, only patients with severe envenoming are at risk of death and sequelae (Otero et al 1992a(Otero et al , 1996(Otero et al , 1999Otero 2014;Otero-Patiño et al 1998Otero-Patiño 2009). Nevertheless, the clinical grading herein described has a temporal validity on admission because the envenoming is a dynamic process which progresses in 10-15 % of the cases after the beginning of antivenom therapy (Otero 2014;Otero-Patiño 2009).…”
Section: Bothrops Bitesmentioning
confidence: 81%
“…In many tropical areas of Latin America, at least 40-50 % of patients receive traditional medicine as first treatment (plants, chemical products, physical methods, prayers, etc.). This and other factors cause a delay in the arrival of those patients to the hospitals; most of them seek Toxinology DOI 10.1007/978-94-007-6288-6_41-1 # Springer Science+Business Media Dordrecht 2014 medical attention 6 or more hours after the bite, thus affecting the prognosis of these cases (Otero et al 1992a(Otero et al , 1996(Otero et al , 1999(Otero et al , 2000aOtero-Patiño et al 1998).…”
mentioning
confidence: 99%
“…In several experimental and clinical trials it has been demonstrated that antivenoms are of limited value to stop edema progression within the first 12-24 h of treatment, while they are highly efficient in restoring blood coagulation status within the same time interval (7,22,23).…”
Section: Discussionmentioning
confidence: 99%